Aroma Profile of the Aerial Parts of Ocimum sanctum L. Harvested at Vegetative and Full Blooming Stages from Three Atitudes of North India. Issue 3 (4th May 2021) - Rana, Lata; Tewari, Geeta; Pande, Chitra
Abstract: To determine the effect of growth stages on the essential oil quality for medicinal and industrial prospective, Ocimum sanctum L. was collected from three different sites of north India at the vegetative and full blooming stage. Soils collected from these sites were analyzed and the results reflected that the pH scale ranged from 6.36 to 6.76, electrical conductivity from 0.51 to 0.64 dS m −1, organic carbon from 4.04 to 5.95 %, and water holding capacity from 35.96–59.02 %. GC/MS analysis of the oils resulted in the identification of total 21, 23, 30, 34, 21, and 31 compounds representing 95.73 %, 98.94 %, and 95.10 % of the oil at vegetative and 97.16 %, 99.54 %, and 94.94 % of the oil at the full blooming stage. The effect was most notable in the essential oil composition at all growth stages. β-Elemene (26.52–57.92 %), eugenol (1.22-45.06 %), ( E )-β-ocimene (0.01-17.74 %), germacrene D (0.04–17.55 %), ( E )-caryophyllene (8.70–39.31 %) and α-copaene (1.24–7.11 %) were the main components of the oils. On the other hand, the predominance of sesquiterpene hydrocarbons (52.30–79.82 %) was higher in both stages of oil composition than followed by others. It was found that during the first harvest, β-elemene (57.92 %) was present as the major compound in the oil while eugenol (45.06 %) was the predominant component in the second harvest.